A Survey on Integrated Access and Backhaul Networks - Zhang, Yongqiang; Kishk, Mustafa A.; Alouini, Mohamed-Slim (Frontiers in Communications and Networks, 2021)
Owing to the utilization of part of the high-frequency band, utilizing part of the large available bandwidth in the high-frequency band, wireless backhauling is a feasible technology with no considerable performance loss. In this context, integrated access and backhaul (IAB) has been proposed by the Third Generation Partnership Project (3GPP) to reduce the expenses related to the deployment of fiber optics for 5G and beyond networks. In this paper, first, a brief introduction of IAB based on the 3GPP release is presented. Then, the existing research on IAB networks based on 3GPP specifications and possible non-3GPP research extensions, such as the integration of IAB to cache-enabled, optical communication transport, and the non-terrestrial networks, are surveyed. Finally, the challenges and opportunities related to the development and commercialization of the IAB networks are discussed.